An Analysis of Clinicopathological Outcomes and the Utility of Preoperative MRI for Patients Undergoing Resection of Mucinous and Non-Mucinous Colorectal Cancer Liver Metastases - Reynolds, Ian S.; Cromwell, Paul M.; Ryan, Éanna J.; McGrath, Erinn; Kennelly, Rory; Ryan, Ronan; Swan, Niall; Sheahan, Kieran; Winter, Des C.; Hoti, Emir (Frontiers in Oncology, 2022)
Background & Aims: Mucinous colorectal cancer has traditionally been associated with high rates of recurrence and poor long-term survival. There is limited published data on outcomes for patients undergoing liver resection for metastatic mucinous colorectal cancer. The aim of this study was to compare the clinicopathological outcomes for patients with mucinous colorectal cancer liver metastases (CRCLM) undergoing liver resection to a matched group of patients with adenocarcinoma not otherwise specified (NOS) and to evaluate the accurary of preoperative magnetic resonance imaging (MRI) at detecting the presence of mucin in liver metastases. Materials & Methods: Patients with mucinous CRCLM undergoing liver resection were matched 1:3 to patients with adenocarcinoma NOS CRCLM. Clinicopathological data from the primary tumour and metastatic lesion were collected and compared between the groups. Hepatic recurrence-free, disease-free and overall survival were compared between the groups. The ability of preoperative MRI to detect mucin in CRCLM was also evaluated. Results: A total of 25 patients with mucinous CRCLM underwent surgery over the 12-year period and were matched to 75 patients with adenocarcinoma NOS. Clinicopathological findings were similar between the groups. Resection of mucinous CRCLM was feasible and safe with similar levels of morbidity to adenocarcinoma NOS. There were no differences identified in hepatic recurrence-free (p=0.85), disease-free (p=0.25) and overall survival (p=0.98) between the groups. MRI had a sensitivity of 31.3% in detecting the presence of mucin in CRCLM. Conclusion: Patients with mucinous CRCLM in this study had similar outcomes to patients with adenocarcinoma NOS. Based on our findings, histological subtype should not be taken into account when deciding on resectability of CRCLM.